2018
DOI: 10.1016/j.jconrel.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-directed liposomal delivery improves the therapeutic index of an immunomodulatory cytokine in controlling autoimmune arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation of the synovial tissue of the joints. Inadequately controlled disease may cause severe joint damage and deformity. Currently, the anti-arthritic drugs are given systemically, and therefore, they are widely distributed to other organs that are not the intended therapeutic targets. Accordingly, using a particular dose/regimen of a drug to achieve an effective local concentration of the drug in arthritic joints may lead to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Regularly observed the severity of arthritis in rats, and grade according to the degree of erythema and paw swelling by 0–4 points as follows (Meka et al., 2018): 0 = no swelling or erythema, 1 = swelling or erythema of the toe joints or toes, 2 = swelling or erythema at the toe joints and toes, 3 = swelling or erythema at the toe joints/toes/ankle joints, 4 = severe swelling or erythema behind the ankle joints. The individual scores of limbs were summed up to give maximum possible score of 8 per mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Regularly observed the severity of arthritis in rats, and grade according to the degree of erythema and paw swelling by 0–4 points as follows (Meka et al., 2018): 0 = no swelling or erythema, 1 = swelling or erythema of the toe joints or toes, 2 = swelling or erythema at the toe joints and toes, 3 = swelling or erythema at the toe joints/toes/ankle joints, 4 = severe swelling or erythema behind the ankle joints. The individual scores of limbs were summed up to give maximum possible score of 8 per mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there was a decrease in IL-1ÎČ and IL-6 levels in serum as well as reduced expression of Flk-1, Flt-4, and HIF-1α in synovium of liposome-triptolide group when compared to arthritic control group [ 184 ]. In a recent study, we have shown that liposomes encapsulating an immunomodulatory cytokine IL-27 and displaying a joint-homing peptide [ 185 ] on their surface are more effective in suppressing AA in rats compared with liposomes containing IL-27 but lacking the peptide on the cell surface as well as free IL-27 [ 186 ]. We propose that IL-27 combined with a natural product such as celastrol [ 186 ] might have an additive or synergistic protective effect against AA, and we plan to test this in the near future.…”
Section: Nanoparticle-based Delivery Of Plant Natural Products Andmentioning
confidence: 99%
“…Originally, synovium targeting emerged as a strategy to minimize the secondary effects of systemic administration of NSAIDs and other anti‐inflammatory therapeutics (Figure 3). Two peptides that bind to inflamed synovial vasculature 107,108 have been discovered via phage display and have shown promising targeting results after systemic administration in small animal models of rheumatoid arthritis 109,110 . The first peptide was discovered by screening the ability of peptides administered intravenously (IV) to specifically bind to the vasculature of human synovium grafted into immunodeficient mice 107 .…”
Section: Targeting For Ia Drug Deliverymentioning
confidence: 99%
“…Another group reported the discovery of a peptide (ADK: CRNADKFPC) able to bind to inflamed synovial vasculature and showed that IV administration of ADK peptide in a rat model of adjuvant arthritis resulted in reduced inflammation scores, decreased T‐cell trafficking and angiogenesis inhibition 108 . Additionally systemic administration of ADK‐functionalized liposomes loaded with the immunomodulatory cytokine IL‐27 resulted in in vivo targeting of arthritic joints and significant reduction in rat paw inflammation compared to nontargeting liposomes or free IL‐27 in a rat model of rheumatoid arthritis 110 . Despite these results, the ADK peptide is also able to bind to inflamed skin 108 and the control scrambled sequence has not been characterized.…”
Section: Targeting For Ia Drug Deliverymentioning
confidence: 99%